DESCRIPTION OF KNOWLEDGE IN ANTIBIOTIC GIVING IN ROSSOAN VILLAGE HEALTH CENTER, ENREKANG DISTRICT, ENREKANG REGENCY - Handayany, Gemy Nastity; Fitri, Nurdia; Basri, Syahrul (Universitas Islam Negeri Alauddin Makassar, 2025)
An adequate understanding on health workers on use antibiotics can prevent the treatment ineffective. Increased risk for the security patient and the spread resistence. The purpose of this research that is, to know the knowledge of midwives in provision of antibiotics for the patient. The kind of research non experiment by using the method case study a qualitative approach. The data using a method of in- depth interviews. The determination of inform with purposive technique. Inform were 6 people consisting of 3 informants midwives and 3 informants patients.Based on the results of the study, the knowledge of midwives' knowledge of rationality in the administration of antibiotics based on 4 T (exact patient, precise indication, proper drug, correct dose) and 1 W (side effect) is still not appropriate because in midwife antibiotics using empirical therapy, the use of antibiotics for empirical therapy is the use of antibiotics in cases of infection that have not been known to the type of bacteria the cause. And rician drug information submitted is the name of the drug, the purpose of therapy, how to take medication with a time interval of 3 x 1 in a day, the drug should be spent and back in case of abnormalities when taking the drug